Ectopic bile duct concomitant with gastric ulcer hemorrhage: report of a case - Yuiko Nagasawa; Masayuki Ohta; Yuki Shitomi; Hiroshi Satoh; Masanori Aramaki (Surgical Case Reports, 2024)
Abstract Background An ectopic bile duct opening into the stomach is a rare congenital anomaly of the biliary system, and thus, there are few case reports with gastric ulcer hemorrhage. Herein, we presented a case of ectopic bile duct concomitant with gastric ulcer hemorrhage. Case presentation A 75-year-old woman was referred to our hospital because she repeatedly vomited blood and had melena. Endoscopic hemostasis was attempted for hemorrhage from a gastric ulcer located on the anterior wall of the antrum. However, the bleeding was difficult to stop, and a laparoscopic distal gastrectomy was performed. Her postoperative course was uneventful. Pathological examination revealed that the bleeding point was an ectopic bile duct. In retrospect, an annual endoscopy performed at her family clinic had revealed a bulge in the same portion of the stomach. Exposure to bile acids from an ectopic bile duct opening can cause gastric mucosal damage and ulceration. Conclusions Ectopic bile ducts opening into the stomach can cause gastric ulcer and hemorrhage. Hemorrhage from a submucosal ridge with ulcer in the stomach may be rarely related to the presence of ectopic bile ducts.